Libraries In The Age Of Technocoloniality: Epistemic Alienation In African Scholarly Communications - Mboa Nkoudou, Thomas Hervé (My University, 2021)
This keynote was delivered during the Critical Approaches to Libraries Conference 2021
Keywords: Technocoloniality; Library; Open Access